Aeroallergen and food IgE sensitization and local and systemic inflammation in asthma. Issue 3 (7th January 2014) - Patelis, A.; Janson, C.; Borres, M. P.; Nordvall, L.; Alving, K.; Malinovschi, A.
Abstract Background We recently reported an independent association between IgE sensitization to food allergens and increased airway inflammation, assessed by fraction of exhaled nitric oxide (FeNO), in a population‐based study (J Allergy Clin Immunol, 130, 2012, 397). Similar studies have not been performed in populations with asthma. The aim of the present study was to investigate the allergic sensitization profile in asthmatics and examine FeNO, airway responsiveness and blood eosinophilia in relation to type and degree of IgE sensitization. Method FeNO, airway responsiveness, blood eosinophil count (B‐Eos) and IgE sensitization to food allergens and aeroallergens were determined in 408 subjects with asthma, aged 10–34 years. Results Asthmatics had higher prevalence of IgE sensitization against all allergens than controls (P < 0.001). Mite, pollen, furry animal, mould and food sensitizations were each associated with increased FeNO, airway responsiveness and B‐Eos in asthmatics. IgE sensitization to mould, furry animals and food allergens was independently related to FeNO (all P < 0.05) after adjustment for age, sex, height, smoking history and medication. IgE sensitization to mould (P < 0.001) and furry animals (P = 0.02) was related to airway responsiveness in a similar model. Finally, IgE sensitization to mould (P = 0.001), furry animals (P < 0.001) and food allergens (P < 0.001) was independently related to B‐Eos. Conclusion Independent effects of IgE sensitization to aeroallergens (furry animals and mould) and food allergens were found on both local and systemic markers of inflammation in asthma. The finding regarding food IgE sensitization is novel, and a clinical implication might be that even food sensitization must be assessed to fully understand inflammation patterns in asthma.